PANTANG LARANG DALAM FENOMENA SOSIAL MASYARAKAT MELAYU - Syah, Efrizal Amarullah (Jurnal Ilmu Budaya, 2011)
Malay culture in Riau is influenced by various elements. The influence affects on Malay tradition, one of them is a tradition called "Pantang Larang" which has existed in the life of Malay society for centuries. This tradition referes to prohibition of doing something since the doer will be punished mentally. This "Pantang Larang" contains educational elements about morality, economy and culture. Since Malay culture is united with Islamic teaching, this "Pantcang Larang" relates to Islam. Ironically, there are many "Pantang Larang" in Riau which do not reflect Islamic teaching due to the big influence of myths and superstitious beliefs.